2021
DOI: 10.3389/fphy.2021.642682
|View full text |Cite
|
Sign up to set email alerts
|

Design of Driving Waveform Based on Overdriving Voltage for Shortening Response Time in Electrowetting Displays

Abstract: A fast response speed of a pixel is important for electrowetting displays (EWDs). However, traditional driving waveforms of EWDs have the disadvantage of long response time. So, a driving waveform, which based on overdriving voltages and charge trapping theory, was proposed in this paper to shorten the response time of EWDs. The driving waveform was composed of an overdriving stage and a driving stage. Firstly, a simplified physical model was introduced to analyze the influence of driving voltages on the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…This scheme could effectively reduce the response time. Lastly, due to the response speed of the oil was increased when the driving voltage was increased, the work showed that overdriving voltage can reduce the response time [61]. The influence of different overdriving voltages on response time was tested in this work.…”
Section: Driving Waveforms For Reducing Response Timementioning
confidence: 99%
“…This scheme could effectively reduce the response time. Lastly, due to the response speed of the oil was increased when the driving voltage was increased, the work showed that overdriving voltage can reduce the response time [61]. The influence of different overdriving voltages on response time was tested in this work.…”
Section: Driving Waveforms For Reducing Response Timementioning
confidence: 99%
“…The driving waveform has influence on the movement of oil [32][33][34]. To comprehend the acceleration ability of oil with the action of driving waveforms in one cycle, these driving waveforms with a different rising slope were designed, as shown in Figure 8.…”
Section: Influence Of Driving Waveformsmentioning
confidence: 99%
“…But the response time of EWDs was limited. Lately, Zeng [18] introduced a 4 ms overdriving stage at 32 V to improve the response speed of EWDs, but the situation of much higher overdriving voltages had not been studied. In addition, it did not give a general method to design a waveform, and the proposed waveform was only limited to the EWD used in its verification.…”
Section: Figure 3 |mentioning
confidence: 99%